1995
DOI: 10.1002/chir.530070416
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective and species‐dependent kinetics of reboxetine in mouse and rat

Abstract: Reboxetine, (RS)-2-[(RS)-alpha-(2-ethoxyphenoxy)benzyl]morpholine methanesulphonate, is a racemic compound and consists of a mixture of the (R,R)- and (S,S)-enantiomers. In this study, brain and plasma levels of both enantiomers were determined in mice and rats after oral administration of reboxetine at doses (1.1 mg/kg, mouse; 20 mg/kg, rat) twice the respective ED50 values in the antireserpine test. Plasma and brain concentrations of each enantiomer were measured up to 6 h postdosing using an HPLC method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…(ϩ)-(S,S)-and (Ϫ)-(R,R)-Reboxetine have been reported to differ by ϳ20-fold in potency for inhibition of norepinephrine uptake (IC 50 values of 3.6 nM and 85 nM, respectively; Dostert et al, 1997). Furthermore, the effects of reboxetine have been reported to result more from the actions of (ϩ)-(S,S)-compared with the (Ϫ)-(R,R)-enantiomer (Benedetti et al, 1995). In contrast, in the current study, no differences were observed between the racemic and (ϩ)-(S,S)-forms of reboxetine with respect to the observed decrease in nicotine self-administration.…”
mentioning
confidence: 99%
“…(ϩ)-(S,S)-and (Ϫ)-(R,R)-Reboxetine have been reported to differ by ϳ20-fold in potency for inhibition of norepinephrine uptake (IC 50 values of 3.6 nM and 85 nM, respectively; Dostert et al, 1997). Furthermore, the effects of reboxetine have been reported to result more from the actions of (ϩ)-(S,S)-compared with the (Ϫ)-(R,R)-enantiomer (Benedetti et al, 1995). In contrast, in the current study, no differences were observed between the racemic and (ϩ)-(S,S)-forms of reboxetine with respect to the observed decrease in nicotine self-administration.…”
mentioning
confidence: 99%
“…Plasma levels of both enantiomers decayed with a terminal half-life of 3.9 ± 0.8 (3.7) h. The AUC to infinite time was higher for the (R,R)-(2,876 ± 1,354 [3,575] ng ⅐ h/ml) than for the (S,S)-enantiomer (1,998 ± 848 [2,368] ng ⅐ h/ml). Mean 0-48 h recovery in urine of the two enantiomers was very low and close to each other, being 1.3 ± 0.7 (0.9) and 1.1 ± 0.7 (0.8)% of the enantiomer dose.…”
Section: Reboxetine Administrationmentioning
confidence: 94%
“…1 Reboxetine has been shown to be a potent and selective inhibitor of noradrenaline uptake in rat hypothalamic synaptosomes, with the (S,S)-enantiomer being more potent (IC 50 = 3.6 nM) than its (R,R)-counterpart (IC 50 = 85 nM). 2 The pharmacokinetic profiles of the two reboxetine enantiomers have been found to differ from each other after a single oral dose in man. 3 After racemic administration (4 mg reboxetine as free base) to nine healthy volunteers mean t max was about 2 h for both enantiomers.…”
mentioning
confidence: 99%
“…It is a non tricyclic antidepressant drug, the (S,S) enantiomer being two times more potent in receptor binding and in in vivo models of norepinephrine re-uptake inhibition than the (R,R) enantiomer. 30,31) Therefore, further pharmacological studies could be performed only with enantiomer (R)-8-PN to increase the panicolytic effect observed for the racemic mixture of 8-PN.…”
Section: )mentioning
confidence: 99%